'You get the quickest and the cheapest stuff you can': Food security issues among low-income earners living with diabetes - Cuesta-Briand, Briand; Saggers, Sherry; McManus, Alexandra (Australasian Medical Journal Pty Ltd, 2011)
Background: Diabetes prevalence is increasing in Australia and worldwide. More than 800,000 Australians live with diabetes, and there are stark inequities in prevalence and clinical outcomes among Indigenous people and low socio-economic groups.The ability to maintain a healthy diet – an essential component of diabetes self-management – is compromised by food availability, accessibility and affordability issues. This paper focuses on food security issues experienced by low-income earners living with type 2 diabetes in Perth, Western Australia. The results presented here are part of a broader qualitative study exploring the impact of socio-economic disadvantage on the experience of diabetes. MethodData were collected through focus groups and semi-structured interviews conducted from October 2008 to November 2009. The sample, comprising 38 participants (Indigenous and non-Indigenous), was recruited from areas with high indices of socio-economic disadvantage in the Perth metropolitan area. Deductive data analysis identified categories from an existing conceptual framework for the relationship between socio-economic position and diabetes health outcomes, while an inductive approach was adopted to identify new themes.ResultsDiet was perceived as the main component of diabetes self-management, and there was a common understanding of the dietary requirements for a person with diabetes. However, access to healthy food was not always realised, as many participants depended on others for food provision and meal preparation and had little control over their diets., and Furthermore, the majority struggled to accommodate the price of healthy food within a limited budget.ConclusionIn this study, low-income earners living with diabetes faced food security issues which limited their ability to implement and sustain recommended dietary changes. Participants reported cost barriers, but also physical barriers relating to functional limitations and lack of transport. This study highlights that the socio-economic circumstances in which the experience of disease of vulnerable populations are embedded need to be understood and addressed in order to reduce the inequities surrounding diabetes outcomes.